2014
DOI: 10.1053/j.jvca.2013.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Considerations for Thoracoscopic Sympathetic Ganglionectomy to Treat Ventricular Tachycardia Storm: A Single-Center Experience

Abstract: Objective The aim of this study was to determine the pertinent anesthetic considerations for patients undergoing surgical sympathectomy for electrical storm (incessant ventricular tachycardia (VT) refractory to traditional therapies). Design This is a retrospective review of a prospective database. Setting This single-center study took place in a university hospital setting. Participants Twenty-six patients were enrolled. Interventions Fifteen patients underwent left-sided sympathectomy, whereas 11 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…We included 14 nonrandomized studies in our final analysis. 5,[11][12][13][14][15][16][17][18][19][20][21][22][23] Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 14 nonrandomized studies in our final analysis. 5,[11][12][13][14][15][16][17][18][19][20][21][22][23] Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Prisma flow diagram for the study selection is shown in Figure 1. We included 14 nonrandomized studies in our final analysis 5,11‐23 . Majority of the studies were from North America.…”
Section: Resultsmentioning
confidence: 99%
“…Thoracic epidural anaesthesia might reduce the incidence of ventricular arrhythmias by blocking cardiac sympathetic fibres. [ 13 ] Stellate ganglionectomy is another option to treat sympathetically mediated VT.[ 14 ] In patients undergoing thoracic surgeries, thoracic epidural infusion is believed to reduce the episodes of tachycardia. [ 15 ] Whenever there is a need for temporary pacing, the cardiologist may be called for intervention.…”
Section: Treatmentmentioning
confidence: 99%
“…long QT syndrome) [81-83]. However, whether such interventions may be used for all ventricular arrhythmias or only a subset is unclear [84-86]. …”
Section: Clinical Correlatesmentioning
confidence: 99%